Bioleaching of lithium from jadarite, spodumene, and lepidolite using Acidiothiobacillus ferrooxidans - Kirk, Rebecca D.; Newsome, Laura; Falagan, Carmen; Hudson-Edwards, Karen A. (Frontiers in Microbiology, 2024)
Lithium (Li) is becoming increasingly important due to its use in clean technologies that are required for the transition to Net Zero. Although acidophilic bioleaching has been used to recover metals from a wide range of deposits, its potential to recover Li has not yet been fully explored. Here we used a model Fe(II)- and S-oxidising bacterium, Acidiothiobacillus ferrooxidans, to extract Li from three different lithium minerals. Bioleaching of Li from the aluminosilicate minerals lepidolite (K(Li,Al)3(Al,Si,Rb)4O10(F,OH)2) and spodumene (LiAl(Si2O6) was slow, with only up to 14 % (around 12 mg/L) of Li released over 30 days. By contrast, At. ferrooxidans accelerated Li leaching from a Li-bearing borosilicate clay (jadarite, LiNaB3SiO7OH) by over 50 % (over 120 mg/L) in 21 days of leaching, and consistently enhanced Li release throughout the experiment compared to the uninoculated control. Fe(II) present in the jadarite-bearing clay acted as an electron donor. Chemical leaching of Li from jadarite using H2SO4 was most effective, releasing around 75 % (180 mg/L) of Li, but required more acid than bioleaching for pH control. Kinetic modelling was unable to replicate the data for jadarite bioleaching after primary abiotic leaching stages, suggesting additional processes beyond chemical leaching were responsible for the release of Li. Biofilm formation and flocculation of sediment occurred exclusively in the experiments with At. ferrooxidans and jadarite. A new crystalline phase, tentatively identified as boric acid, was observed to form after acid leaching of jadarite. Overall, the results demonstrate the potential for acidophilic bioleaching to recover Li from jadarite, with relevance for other Li-bearing clay deposits.